Nanomaterial processing strategies in functional hybrid materials for wastewater treatment using algal biomass - Eroglu, Ela; Raston, C. (Wiley, 2017)
© 2017 Society of Chemical Industry.Algal cultivation has tremendous potential in wastewater treatment, and its simultaneous biomass production has advantages for the production of value added products such as biodiesel, fertilizers and pharmaceuticals. Some obstacles to obtaining a productive biological water treatment and bioenergy system are the harvesting and processing of biomass. Such issues can be addressed using nano-bio hybridization approaches by simplifying the microbial harvesting step along with increasing the efficiency of wastewater treatment. This review highlights studies within our research group that are based on the fabrication of functional hybrid materials using algal biomass, including: (i) electrospun nanofibers; (ii) laminar nanomaterials; and (iii) magnetic nanoparticles impregnated in a polymer. All of these techniques have been used for the removal of waste pollutants such as nitrate and phosphate ions. The multidisciplinary techniques have potential to provide effective algal culture systems for industrial applications, while having a significant impact on wastewater treatment.